Using interactive digital technology to predict and prevent childhood overweight - Rose, Jennie; Redsell, Sarah A.; Wharrad, Heather; Siriwardena, A. Niroshan; Swift, Judy A.; Dilip, Nathan; Weng, Stephen F.; Atkinson, Pippa; Ablewhite, Joanne; Watson, Vicki; Glazebrook, Cris (Wiley, 2017)
Background: Obesity risk factors can be identified during infancy, providing an opportunity for early intervention. ProAsk is an interactive digital intervention that supports health professionals to quantify and communicate an infant's overweight risk status, prompting discussion of parental strategies to reduce future risk.